Optimasi Primer : Suhu Annealing untuk Deteksi Gen Matrix Virus Influenza A Menggunakan Polymerase Chain Reaction (PCR) - Natalia Turnip; Nova Dilla Yanthi; Dwi Hilda Putri (Universitas Cokroaminoto Palopo, 2026)
Influenza A virus (IAV) is a pathogen that attacks the respiratory tract in humans and animals, which can be a threat to public health. This virus has a number of genes that are targeted by PCR for diagnostic detection purposes, one of which is the matrix gene. Detection of the matrix gene in the Influenza A virus from DNA/RNA genetic material can be done using the polymerase chain reaction (PCR) technique. One of the stages that determines the success of the PCR process is the annealing stage, for which the optimum temperature and cycle are required for primer attachment in the annealing stage. This research is a descriptive study towards an experiment conducted in June 2025 at the Bacteriology Laboratory of the Research and Innovation Agency (BRIN) KST. Soekarno Cibinong. The results obtained showed that the optimum temperature for matrix gene amplification in the Influenza A virus using the forward primer FluAV M-U44 and reverse primer FluAV M-L287 was 53.5 °C, 54 °C, and 54,5 °C and 35 cycles were evidenced by the formation of a fairly bright band in the electrophoresis results.